2022
DOI: 10.1007/s00383-022-05130-1
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting mechanical complications of central venous access devices in children

Abstract: Purpose Factors leading to mechanical complications following insertion of central venous access devices (CVADs) in children are poorly understood. We aimed to quantify the rates and elucidate the mechanisms of these complications. Methods Retrospective (2016–2021) review of children (< 18 years old) receiving a CVAD. Data, reported as number of cases (%) and median (IQR), were analysed by Fisher’s exact test, chi-squared test and logistic regre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
3
7
0
Order By: Relevance
“… 17 Data from this study showed that complications resulted in premature device removal in 25% of cases, even by adopting approved Hickman CVC management procedures. This finding is similar to a recent study by Zhang et al 18 Van den Bosch et al 19 reported that ~37% of Hickman CVCs in pediatric cancer patients were prematurely removed owing to complications. However, a lower percentage of the overall complications of ~10% that led to the premature removal of the Hickman CVC was reported by Perdikaris et al 17 The overall complications recorded per 1000 catheter days for Hickman lines in our study of 1.42/1000 catheter days are lower compared with 2 retrospective studies on adults for this type of CVC.…”
Section: Discussionsupporting
confidence: 91%
“… 17 Data from this study showed that complications resulted in premature device removal in 25% of cases, even by adopting approved Hickman CVC management procedures. This finding is similar to a recent study by Zhang et al 18 Van den Bosch et al 19 reported that ~37% of Hickman CVCs in pediatric cancer patients were prematurely removed owing to complications. However, a lower percentage of the overall complications of ~10% that led to the premature removal of the Hickman CVC was reported by Perdikaris et al 17 The overall complications recorded per 1000 catheter days for Hickman lines in our study of 1.42/1000 catheter days are lower compared with 2 retrospective studies on adults for this type of CVC.…”
Section: Discussionsupporting
confidence: 91%
“…Our center’s experience aligns with literature findings, highlighting the essential role of comprehensive medical personnel training. The frequency of early complications in the pediatric population occurring in the Poznan center was similar to international literature data for both adult and pediatric patients ( 5 , 29 34 ). The incidence of early complications, particularly pneumothorax, correlated with the operator’s experience, being higher among physicians in training.…”
Section: Discussionsupporting
confidence: 84%
“…The incidence of complications related to Broviac catheters in our population was higher than in the literature. [5] Previous studies showed that the complication rate was less than 20%. [5,6] This may be due to our population, which includes critically ill neonates and young infants with severe prematurity and comorbidities, but also to the quality of healthcare.…”
Section: Discussionmentioning
confidence: 98%
“…[5] Previous studies showed that the complication rate was less than 20%. [5,6] This may be due to our population, which includes critically ill neonates and young infants with severe prematurity and comorbidities, but also to the quality of healthcare. [7,8] The management of these tunneled catheters needs special nursing skills.…”
Section: Discussionmentioning
confidence: 98%